Technological Pedagogical and Content Knowledge of Biology Prospective Teachers - Evi Suryawati; Mariani Natalina Linggasari; Arnentis Arnentis (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
This research was conducted for analyzing Technological Pedagogical and Content Knowledge (TPACK) of biology prospective teachers in Riau Province. The study was carried out to fulfill Indonesian Government’s policy on Indonesian Qualification Framework (IQF) 6-Level. This development research aimed to analyze, design and develop a model to enhance the competency and competitiveness of Education College graduates to meet their professional, social and industrial needs. This paper discussed a preliminary study of the developed models for strenghtening the prospective teachers from Biology Education Departement, conducted through a survey of 243 students from four different colleges of education in Riau Province. The data were collected through a test and interview. The instruments used contained seven variables of knowledge, namely Technology, Paedagogy, Content, Technological Paedagogy, Technological Content, Technological knowledge and TPACK. The instruments was improved through their validity and reliability test. The TPACK performance of Prospective Biology teachers seemed low. Based on the need analysis two products will be generated. First, a lesson design and the second was a work books. This study had an implications for increasing the competence of biology education graduates. The lesson design and competency test instruments could be used for College of Biology Education and teacher professional education in developing competency test for selection system. The TPACK workbook could be used as teacher enrichment in sustainable profession development such as classroom action research, learning innovation contest, and science teacher olympiad.